Infrared Image Enhancement: A Review - Qingwang Wang; Pengcheng Jin; Yuhang Wu; Liyao Zhou; Tao Shen (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
Under special conditions such as night, rain, and fog, visible light imaging technology often performs poorly, while radar and other imaging technologies are limited due to their high costs. Infrared imaging technology, based on the principle of thermal radiation, can provide clear imaging effects under these extreme conditions and has a relatively low cost of use. Therefore, it has been widely applied in various fields, including military, medical, industrial, and agricultural applications. However, due to the limitations of infrared wavelengths and imaging technology, traditional infrared imaging devices struggle to capture rich texture information, leading to infrared images that lack texture details and have low resolution, which significantly restricts the further research and application of infrared imaging technology in various fields. In recent years, with the widespread attention to infrared imaging technology, researchers have proposed various new infrared image enhancement techniques. Despite this, the lack of texture information in ordinary infrared images leads to the enhancement effect of existing technologies being unsatisfactory. Therefore, we have conducted a systematic investigation of the research advancements in the field of infrared image enhancement, encompassing infrared image enhancement methods, related datasets, and evaluation metrics, with the aim of exploring a research solution that could potentially break through current technological limitations. Based on these investigations, we have evaluated the performance of various representative infrared image enhancement methods, with the hope of providing a reference for future research. In addition, this article also provides a comprehensive introduction to the potential applications of infrared image enhancement technology and discusses significant research directions for the future.